Listening and Vocabulary Gains via Arabic Song Media: A Two-Cycle Classroom Study in Grade X - Kesuma, Guntur Cahaya; Hijriyah, Umi; Erlina; Sufian, Muhammad; Rimadhona (Yayasan Darussalam Bengkulu, 2023)
This article reports a classroom study examining whether Arabic song media can improve Grade-X students’ listening skills and vocabulary mastery. Drawing on a descriptive qualitative design with two iterative cycles (Plan Act Observe Reflect), the study was implemented in one intact class (n = 29) at a private senior high school. Data sources comprised observation fieldnotes, lesson artefacts (tests, rubrics), and teacher student feedback across cycles. Baseline assessment showed only 7 students meeting the minimum criterion in listening and 12 in vocabulary. After Cycle I, the number of students meeting the criterion rose to 19 (≈65%) for listening and 17 (≈59%) for vocabulary; after Cycle II, gains reached 26 (≈90%) and 25 (≈86%), respectively. Pedagogically, improvements were associated with explicit objectives, focused listening tasks, and iterative feedback; practically, song media increased engagement and supported repeated, meaningful exposure to target lexis. The study concludes that Arabic songs, when embedded in clear task designs and continuous feedback, can deliver substantial short-term gains in listening and vocabulary for Grade-X learners. Limitations include the single-class scope and lack of a control group; implications and future directions are outlined.